Hidden trauma: shedding light on the relationship between gun violence and infertility - Amanda J. Adeleye, M.D; Tanya W. Kristof, M.D; Aaditi G. Naik, B.S; Sandra Madueke Laveaux, M.D., M.P.H; Jennifer Cone, M.D; Sarah Faris, M.D; Tanya L. Zakrison, M.D., M.P.H (Elsevier, 2022)
Objective: To study the existing data on the relationship between penetrating abdominopelvic injuries and fertility guidance on managing fertility concerns of these patients using a case report and scoping review. Design: Case report and scoping review. Setting: Not applicable. Patient(s): People who have experienced abdominopelvic trauma from gun violence or in the course of combat. Intervention(s): None. Main Outcome Measure(s): We extracted case report data from electronic health records. We performed a scoping review using PubMed and Scopus. Search terms were related to penetrating abdominopelvic trauma, gunshot wounds (GSW), war, and fertility/infertility. We evaluated the study year, age and race, mechanism of injury, fertility outcomes, and how fertility concerns were addressed with patients who experienced penetrating abdominopelvic trauma. Result(s): In the case report, the couple had 10 years of infertility. The male partner experienced an abdominopelvic GSW before attempting to conceive. After evaluation, he was diagnosed with retrograde ejaculation. He recalled being advised that his GSW might affect his future fertility. The couple has discontinued care.For the scoping review, 879 sources were identified and 25 studies were included in the review. Among the studies conducted in the United States, most patients included were African American.Eighty-eight percent (n = 22) of the sources acknowledged the importance of fertility or used fertility-related outcome measures. One study commented on how to address fertility concerns with victims of abdominopelvic penetrating trauma. Conclusion(s): There is a paucity of data on the intersection of penetrating abdominopelvic injuries and fertility or guidance on how to discuss fertility issues with patients.